Analisis Keefektifan Pembelajaran Blended Learning Pasca Pandemi Covid - Akmal Hidayat; Muh. Sunan Jaya Irmawan; Puang Intan Maylani; Muhammad Fatwa Ma’arij; Andi Shelma Putri Azzahra (Sakura Digital Nusantara, 2023)
Corona virus or Covid-19 that occured in Indonesia have the government made a statement to minimize all activites for temporary including schools that are have to implementing online learning. Educators are required to prepare a learning system that effective and innovative, that include blended learning method. Therefore, this study aims to analyze the effectiveness of blended learning in post-pandemic. This study uses quantitative research methods and collecting data by made questionnaire and spread it in Makassar State University. Based on facts from literature, a conclusion has been made that blended learning method is effectively applied because it makes easier for students to learn, such as flexibly and independently.